Grebek Surowiti dan Festival Bandeng: Harmoni Tradisi Religi dan Penggerak Ekonomi di Gresik - af'idah, maslama nur (Maliki Interdisciplinary Journal, 2025)
Gresik, located on the coast of East Java, has a rich cultural heritage, encompassing both religious and economic aspects. The two main traditions in the city, namely Grebeg Surowiti and the Bandeng Festival, not only preserve spiritual values, but also make significant contributions to the regional economy. Grebeg Surowiti, which aims to honor Sunan Kalijaga, presents an event full of religious meaning and social togetherness. On the other hand, the Bandeng Festival supports the fisheries and tourism sectors through various cultural and economic attractions. This article examines how the two traditions unite religious and economic aspects and their impact on strengthening the cultural identity and welfare of the Gresik community. The Milkfish Festival has a significant impact on the regional economy by promoting the fisheries sector, attracting tourists, and creating opportunities for MSMEs to improve their businesses.